2021
DOI: 10.48550/arxiv.2110.15059
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CLASS_GWB: robust modeling of the astrophysical gravitational wave background anisotropies

Nicola Bellomo,
Daniele Bertacca,
Alexander C. Jenkins
et al.

Abstract: Gravitational radiation offers a unique possibility to study the large-scale structure of the Universe, gravitational wave sources and propagation in a completely novel way. Given that gravitational wave maps contain a wealth of astrophysical and cosmological information, interpreting this signal requires a non-trivial multidisciplinary approach. In this work we present the complete computation of the signal produced by compact object mergers accounting for a detailed modelling of the astrophysical sources and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 132 publications
(182 reference statements)
1
7
0
Order By: Relevance
“…All these terms have been the subject of intense study in recent years and both astrophysical and primordial contributions have been modelled extensively (see for example [107][108][109] for independent calculations of astrophysical background anisotropies and [50,102,110] for examples of primordial ones). The propagation term is often assumed to be negligible in the case of astrophysical backgrounds or it is directly included as part of the source term; in [111,112], it is expressly estimated and shown to account for at most ∼10% of the total anisotropy. In the case of a truly primordial background dating back as far as or before the CMB, however, this term will be considerably larger and will be comparable to the intrinsic anisotropies at large scales as shown in [100].…”
Section: Anisotropies In Stochastic Backgroundsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these terms have been the subject of intense study in recent years and both astrophysical and primordial contributions have been modelled extensively (see for example [107][108][109] for independent calculations of astrophysical background anisotropies and [50,102,110] for examples of primordial ones). The propagation term is often assumed to be negligible in the case of astrophysical backgrounds or it is directly included as part of the source term; in [111,112], it is expressly estimated and shown to account for at most ∼10% of the total anisotropy. In the case of a truly primordial background dating back as far as or before the CMB, however, this term will be considerably larger and will be comparable to the intrinsic anisotropies at large scales as shown in [100].…”
Section: Anisotropies In Stochastic Backgroundsmentioning
confidence: 99%
“…It was found that the angular resolution of LISA for stochastic signals highly depends on their SNR as a function of frequency, as the detector response varies greatly as a function of the latter. The stochastic signals compete with the detector noise, which at low SNR dominates the modes of the Fisher information matrix (112). Beyond this, the angular resolution at which LISA "sees" the signal is diffraction-limited; hence, the higher the frequency, the better the angular resolution will be.…”
Section: Stochastic Searches With the Laser Interferometer Space Antennamentioning
confidence: 99%
“…Models predict that the GW background will present anisotropies due to the nature of spacetime along the line of sight, and for the astrophysical contribution, due to the local distribution of matter and the finitness of the number of sources. The past years a lot of work has been done to characterize anisotropies in particular in the background from CBCs [86][87][88][89][90][91][92][93][94][95].…”
Section: Anisotropymentioning
confidence: 99%
“…All these terms have been the subject of intense study in recent years and both astrophysical and primordial contributions have been modelled extensively (see for example [108][109][110] for independent calculations of astrophysical background anisotropies and [50,103,111] for examples of primordial ones). The propagation term is often assumed to be negligible in the case of astrophysical backgrounds or it is directly included as part of the source term; in [112,113], it is expressly estimated and shown to account for at most ∼10% of the total anisotropy. In the case of a truly primordial background dating back as far as or before the CMB, however, this term will be considerably larger and will be comparable to the intrinsic anisotropies at large scales as shown in [101].…”
Section: Anisotropies In Stochastic Backgroundsmentioning
confidence: 99%